Development of Teaching Materials for Dance Music Courses Based on Project Based Learning Containing QR Codes - Irwansyah Irwansyah; Inggit Prastiawan (Universitas Negeri Medan, 2023)
This research aims to develop Project Based Learning-Based Teaching Materials containing QR Codes for the Dance Music course that are valid and effective in improving the learning outcomes of Dance and Performing Arts Study Program students. The research method used is development research with a 4D (Four-D) development model which consists of four stages, namely: 1) Define, 2) Design, 3) Development and 4) Disseminate. The data collection techniques that will be used are expert validation sheets, response questionnaires and student learning outcomes instruments. The results of this research are as follows (1) Producing Project Based Learning-Based Teaching Materials containing QR Codes in the Dance Music course which are suitable for use with an average percentage of expert validation results of 89.28% in the